A study of prevalence of hypertension and socio-demographic factors in urban slum, Maharashtra - Sawase, Gautam B.; Kumthekar, Sunayana G.; Salphale, Shweta N.; Doibale, Mohan K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension is the commonest cardiovascular disorder, posting a major public health problem of the world and especially to population in socio-economic and epidemiological transition. Around 7.5 million deaths or 12.8% of the total of all annual deaths worldwide occur due to high blood pressure. It is predicted to be increased to 1.56 billion adults with hypertension in 2025. In India there is 24-30% of prevalence of hypertension in urban areas and 12-14% in rural areas. The objectives of the study were to find out the prevalence of hypertension in study population of 18 years and above and to study some socio-demographic factors affecting hypertension. Methods: A community based cross sectional study was carried out in urban slum area, under urban field practice area of a Govt. Medical College & hospital. Sample size of 360 participants of age more than 18 yrs residing in study area taken. Data collected by using systematic random sampling by house to house visit. A semi-structured & pretested questionnaire used to interview the patients after obtaining their consent. The data was analyzed using SPSS version 23. Appropriate statistical tests were applied. Results: The overall prevalence of hypertension was 30.5%. Out of 360 subjects, 47 (13%) found elevated hypertensive. Out of 110 hypertensive population nearly 53 (48%) were in older age group, nearly 60 (55%) were illiterate and 53 (48%) were unskilled workers out of 110 was found statistically significant (p<0.05). Conclusions: Prevalence of hypertension found to be 30.5%. Some socio-demographic factors like age, sex, education, occupation were statistically significant (p<0.05).